ANALISIS KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR NEGERI 001 SUNGAI PINANG - Maimunah Maimunah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The teacher plays a very important role both in planning and implementing the learning process. Therefore teachers must have professional competence that can support the ability in planning and implementing in the learning process. this research was conducted at SDN 001 Sungai Pinang. The purpose of this study was to determine how much the professional competence of teachers in Sungai Pinang 001 Elementary School. This research is a school action research. Data collection techniques used in this study were questionnaire or questionnaire techniques. From the results of the study showed that, teacher professional competence seen from the indicators mastering the competency standards and basic competencies obtained an average percentage of 71.5% good category. Indicators of developing learning materials that are taught creatively, obtained an average percentage of 75.7% good category. Indicators of developing professionalism in a sustainable manner can be seen that the average percentage reaches 80.6% good category. Indicators utilizing information and communication technology, obtained an average percentage of 81.4% in the excellent category. Based on the results of the above research, it can be concluded that the professional competence of SDN 001 Sungai Pinang Teachers, Hulu Kuantan District, Kuantan Singingi Regency is classified as good